2020
DOI: 10.3899/jrheum.190602
|View full text |Cite
|
Sign up to set email alerts
|

Serum MicroRNA Signature as a Diagnostic and Therapeutic Marker in Patients with Psoriatic Arthritis

Abstract: Objective MicroRNAs (miRNAs) are small endogenous regulatory RNA molecules, which have emerged as potential therapeutic targets and biomarkers in autoimmunity. Here, we investigated serum miRNA levels in Psoriatic arthritis (PsA) patients and further assessed a serum miRNA signature in therapeutic responder versus non-responder PsA patients. Methods Serum samples were collected from healthy controls (n=20) and PsA (n=31) and clinical demographics obtained. To examine circulatory miRNA in serum from HC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
(45 reference statements)
2
34
1
Order By: Relevance
“…In order to compare the miRNA signature of RA and healthy sera, a specific panel of 68 miRNAs, known to be associated with immune dysfunction ( 14 ), was selected for multiplex miRNA analysis of serum from HC donors (N = 20) and RA patients that were naïve to treatment (N = 50). The FirePlex Analysis Workbench software was used to analyze and determine significant differences in miRNA expression, between RA and HC, and generate heatmaps.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to compare the miRNA signature of RA and healthy sera, a specific panel of 68 miRNAs, known to be associated with immune dysfunction ( 14 ), was selected for multiplex miRNA analysis of serum from HC donors (N = 20) and RA patients that were naïve to treatment (N = 50). The FirePlex Analysis Workbench software was used to analyze and determine significant differences in miRNA expression, between RA and HC, and generate heatmaps.…”
Section: Resultsmentioning
confidence: 99%
“…Patient blood was collected in anticoagulant-free tubes and processed within 1 h of collection as follows: samples were centrifuged at 2,000 g for 10 min at room temperature to isolate the serum which was transferred to RNase- and DNase-free tubes. The FirePlex Circulating miRNA Immunology Fixed Panel ( Supplementary Table 3 ) (Abcam, Cambridge, UK) was selected for multiplex miRNA analysis of 68 miRNAs in serum as previously described ( 14 ). This panel was utilized to focus on miRNA associated with immune cell dysfunction in autoimmune diseases, and included miRNA that have been previously identified to be associated with RA, either by expression in serum/tissue/cells or associated with immune cell/synovial fibroblast dysfunction ( 14 , 17 20 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An advantage of this method is that it allows quantification directly from biofluids, starting from 10 μL, without the need for miRNA extraction or processing. The Fireplex platform has been recently applied for miRNA biomarker studies in different diseases, including psoriatic arthritis, Duchenne muscular dystrophy and cardiac disease, although an extensive literature is still lacking due to the novelty of the technique [ 150 , 151 , 152 ]. In the oncologic field, Leng et al showed a good concordance of measures obtained with Fireplex, performed directly on plasma samples, compared to the measures obtained by qPCR, upon quantification of 11 specific miRNAs as putative lung cancer biomarkers [ 153 ].…”
Section: Direct Methods For Mirna Measurement From Biofluidsmentioning
confidence: 99%